PERBANDINGAN HARGA SAHAM PT BANK NEGARA INDONESIA (PERSERO) TBK SEBELUM DAN SESUDAH PANDEMI COVID-19 DI INDONESIA - Agizka Yolanda; Andi Hasryningsih Asfar (Universitas Bina Bangsa, 2021)
Stock price is a very important factor for see company value, a high stock price in the company can be said that the company is in good condition, on the other hand, if the stock price of a company is falling, it can be said the company is not good which makes the value of the company go down and can cause investors not to buy the campany’s stock. The purpose of this study was to compare the stock price of PT Bank Negara Indonesia (Persero) Tbk before and after the Covid-19 pandemic in Indonesian for a period of 12 months before and 12 months after the Covid-19 pandemic was confirmed in Indonesian, namely on March 2, 2020. The research method used is descriptive method with qualitative research and uses comparative method. The results of the study using the paired sample t-test showed that the average stock price before the Covid-19 pandemic was IDR 8,114.58 and after the Covid-19 pandemic was IDR 5,088.33, this means that there is a difference in the stock price of PT Bank Negara Indonesia, a significat periode of 12 months before and 12 months afrer the Covid-19 pandemic in Indonesian. The conclusion obtained is that there is a negative impact of the Covid-19 pandemic on the stock price of PT Bank Negara Indonesia (Persero) Tbk